2012
DOI: 10.3177/jnsv.58.161
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Improves Biochemical Indices Associated with Symptoms of Atopic Dermatitis-Like Inflammation in NC/Nga Mice

Abstract: Summary We aimed to define whether vitamin E improves biochemical indices associated with symptoms of atopic dermatitis-like inflammation in NC/Nga mice. After picryl chloride (PC) application to their backs, changes in the content of thiobarbituric acid reactive substances (TBARS) and vitamin E, as well as the activity of antioxidant enzymes (superoxide dismutase (SOD), glutathione peroxidase (GSHPx) and catalase) were analyzed in the serum and skin of NC/Nga mice during a symptomatic cycle. The levels of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Additionally, ROS has been shown to stimulate the inflammasome, promoting the maturation of proinflammatory cytokines such as IL-1b [27,28]. Consistent with these observations, many anti-oxidants, such as natural flavonoids isolated from herbal medicines (vitamin C, vitamin A, vitamin E and N-acetyl cysteine) and anti-oxidant enzymes, have been shown to alleviate inflammatory responses [29][30][31][32][33][34][35][36], supporting ROS as a promising target for treating chronic inflammatory diseases. Here, we review about one of cellular anti-oxidant enzyme, extracellular superoxide dismutase (SOD3) as a potential biomedicine and its application for treatment against inflammatory diseases.…”
Section: Inflammation and Oxidative Stressmentioning
confidence: 89%
“…Additionally, ROS has been shown to stimulate the inflammasome, promoting the maturation of proinflammatory cytokines such as IL-1b [27,28]. Consistent with these observations, many anti-oxidants, such as natural flavonoids isolated from herbal medicines (vitamin C, vitamin A, vitamin E and N-acetyl cysteine) and anti-oxidant enzymes, have been shown to alleviate inflammatory responses [29][30][31][32][33][34][35][36], supporting ROS as a promising target for treating chronic inflammatory diseases. Here, we review about one of cellular anti-oxidant enzyme, extracellular superoxide dismutase (SOD3) as a potential biomedicine and its application for treatment against inflammatory diseases.…”
Section: Inflammation and Oxidative Stressmentioning
confidence: 89%
“…Studies have demonstrated that antioxidants such as quercetin (Que) and cromolyn inhibit release of inflammatory mediators including histamine, leukotrienes, IL-6, IL-8, and TNF release from mast cells in vitro [48]. In vivo studies reveal that vitamin E, an antioxidant, improves atopic dermatitis-like inflammation [49]. Therefore, the anti-inflammatory effect of apigenin could be due to its antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…The role of vitamin E in relieving inflammation and erythema was studied by Hayashi et al [16] using an NC/Nga mouse model. In their study, mice were subcutaneously injected in their backs with a 4% α-TP (200 mg/kg body mass) every other day for 2 weeks.…”
Section: Preclinical Evidence From Animal Studiesmentioning
confidence: 99%
“…T3 has been shown to display a superior antioxidant effect as compared to TP due to its unsaturated and isoprenoid side chain [13-15]. Apart from its antioxidant activity, vitamin E is able to suppress inflammation and upregulate gene expression of keratinocyte differentiation markers, suggesting its potential as a therapeutic agent against AD [16, 17].…”
Section: Introductionmentioning
confidence: 99%